The properties and their effects of Tijuana metropolitan network - Valencia García, Bélgica Jazmín; CETYS Universidad (Tijuana, B.C., 2020)
Tijuana is the 6th largest city in Mexico. Due to its social - geographic characteristics, major avenues and arteries are often congested. Since 2006 and early 2018 onward, Tijuana’s public transport fleets have undergone major renovation, by replacing small capacity vehicles, vans, and taxis, with larger capacity ones (busses). However, the city transport network has been analyzed in less degree. In order to understand its state, we analyze the transport network structural properties, node importance and robustness level. Among the major findings, we find that for a commuter traveling along the network diameter or radius requires in average 16 and 10 route transfers correspondingly. Four, out of nine, delegations concentrate the most important nodes. 80% of the Tijuana Mass Transit network can be disconnected with less 1.5% of nodes under random failures or target attacks.
T3-2020
Tesis (Maestría) - CETYS Universidad
Keywords: Ingeniería; Transport Network; Structural properties; Spatial analysis; Campus Tijuana